Identification of lncRNA HCCAT5 as a Novel Biomarker for Gastric Cancer - Nazila Saedi Alvaroliya; Seyedeh Hayla Jahanshahi; Nazli Khajehnasiri; Fatemeh Zeinali Sehrig; Adel Abdi (International Journal of Genomics)
Conclusions: The lncRNA HCCAT5 is implicated in advancing the development of GC. Consequently, it could be considered a potential target for therapeutic interventions and a prognostic biomarker for GC patients.